FILANTROPI MENURUT PERSPEKTIF AL-QUR’AN: ANALISIS DALAM MENYIKAPI PERMASALAHAN KESENJANGAN EKONOMI UMAT - Arief, Suyoto; Fikri, Achmad Banding Abdullah; Wibisono, Vina Fithriana (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
Philanthropy is a voluntary behavior that aims to benefit the community, whether done independently or institutionally. However, even so, philanthropy that comes with its new transformation from classical to modern (social purposes) which is able to have a positive impact on the economic gap of the people, there is a need to revitalize the meaning of philanthropy not just karitas, which actually must be the basis for the attitude of behavior of all kinds of philanthropic activities, namely presenting philanthropy based on the Qur'anic perspective. Therefore, this study aims to explore the concept of philanthropy in the Qur'anic perspective in addressing the problem of people's economic disparities. The method used is a qualitative research method using library research. The results of this study indicate that philanthropy in the Qur'anic perspective can be used as a reference in addressing all aspects of life, one of which is the problem of economic inequality. The Qur'an has a significant role in the development of Islam and human civilization. The configuration of Qur'an-based philanthropy is through zakat, infaq, sadaqah and waqf which are seen as charitable movements that provide support to help others fairly (sportive), which are able to empower in the long term. Thus, if this philanthropy is implemented properly according to Qur'anic principles, it will reduce the economic gap between the rich and the poor and create a balance in the living standards of a prosperous society.